(untitled) (Medico Legal Update, 2020)
A descriptive study has been used the evaluating science teachers’ knowledge towards mumps disease in primary schools. A probability (simple random sample) the sample consisted of 60 science teachers from 60 primary schools in Holy Kerbala city, during the period of January 2018 to the end of June 2019. The questionnaire involved two-part: the first, demographic data of teachers such as age, gender, and specialization, level of education, years of employment, participation in training course or workshop toward communicable diseases and second part, concerning teachers’ knowledge about mumps in primary schools were comprised of (36) items divided to (6) items related to knowledge about anatomy and physiological of salivary glands, general knowledge about mumps (5) items, knowledge about signs and symptoms of mumps disease (7) items, knowledge about diagnosis and complications of mumps disease (6) items, knowledge about mode of transmission for mumps infection (6) items, knowledge about prevention and treatment of mumps disease. The data was collected by a questionnaire which consisted of two parts, the first part consists socio-demographic data, second part was about the knowledge of mumps disease which consist of (36) items scale of knowledge about mumps disease. In the present study, data were analyzed through the use of statistical package for social sciences (SPSS), version 24. The finding of the study indicated that most of the teachers who participated in the study were female, most of them graduated from institutes and they have an extremely low level of knowledge toward mumps ranges between poor and fair. The study recommends encouraging teachers’ participation in the health education program, especially programs that deal with communicable diseases because the risk of spread these diseases among the school community.